Catalytic and Noncatalytic Mechanisms in Steam Gasification of Char from the Pyrolysis of Biomass - Kajita, M.; Kimura, T.; Norinaga, K.; Li, Chun-Zhu; Hayashi, J. (American Chemical Society, 2010)
Steam gasification of chars from the pyrolysis of a Japanese bamboo and cedar was studied using a reactor that enabled experimental definition of the gas composition in the vicinity of gasifying char particles. Intraparticle diffusion of neither steam nor the product gases influenced the kinetics of gasification. The chars underwent noncatalytic and catalytic gasification in parallel. The noncatalytic gasification, in which kinetic parameters were successfully defined by those for the gasification of the acid-washed char, was first-order with respect to the amount of residual carbon over the entire range of char conversion. In consequence of this, contribution of the catalytic gasification was quantified as a function of the char conversion. Among the inherent alkali and alkaline earth metallic species, potassium (K) played the major catalytic role and its overall activity changed via a maximum in the course of gasification, suggesting the presence of optimum sizes of clusters or particles of K catalyst. The noncatalytic and catalytic reactions obeyed respective Langmuir−Hinshelwood mechanisms that involved inhibition by H2.